INFORMALISASI DAN MASALAH SOSIAL TENAGA KERJA DI INDONESIA DALAM KAJIAN HUKUM (Studi Kasus PHK sebagai Efek Digitalisasi di Kabupaten Cirebon Tahun 2019) - Urip Giyono (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
The Industrial Revolution 4.0 has changed the landscape of all fields in the world, including Cirebon Regency which also feels its impact, therefore global change requires humans to be able to develop their abilities more broadly. One of the labor issues that need to be considered and resolved is the lack of competence and competitiveness of Indonesian workers. Facing the industrial revolution 4.0, the workforce in Cirebon Regency is deemed not to have sufficient readiness and skills. This paper uses Lourdes Beneria and Maria Floro studies which have examined the changes in the informalisation of the labor market in most countries such as Bolivia, Ecuador, Thailand and the Philippines, through the analysis unit of home women workers. and a qualitative method blended between case studies and phenomenology by examining Information and social issues of workers in Indonesia on legal studies (case study of Layoffs as a digitalization effect in Cirebon District 2019).